The Effect of Spatial Distribution of Public Amenities on Residential Property Rental Value - Victor Markus; Pawam Martins Steve (International Journal of Land, 2026)
In major cities around the world, the rental value has indeed been increasing at an unprecedented rate because of the rising demand for residential properties in urban areas. Residential building characteristics, neighborhood characteristics, accessibility factors, and amenities are all factors that influence residential rental value. These amenities lead to rent differentials. The links that exist between residential property rental values and various physical and locational dwelling features, amenities, and so on are valued by Real Estate Valuers, planning authorities, and policymakers. When all these relationships are established, for instance, valuers will be assisted in allocating premiums to various housing and locational characteristics. To maximize return in the form of rent by private investors and property tax or income tax by public authority there have been efforts to provide basic/public amenities and improve the existing ones to ease the living condition of the occupants and create an incentive to the tenant and increase their willingness to pay the rack-rent. This paper seeks to evaluate the effect of the spatial distribution of public amenities on residential property rental value with the view to ascertaining its impact on rent differential using data obtained through questionnaires administered on tenants in the Kaduna Metropolis. The study distributed 400 questionnaires to local individuals using a random selection technique. Data were analyzed using descriptive and inferential statistics. Findings revealed an uneven distribution of the eight (8) public amenities across the study area with wide difference in their state or condition. Kaduna Township and Ungwan Rimi-Malali have the public amenities in good condition than other sub-areas. The uneven distribution of public amenities and their condition resulted in rent differentials within the Kaduna Metropolis. In order to maximize return in the form of rent by private investor and property tax or income tax by public authority there is need to provide these amenities and improve the existing ones in order to ease the living condition of the occupants and create an incentive to the tenant and increase his willingness to pay the rack rent.
Keywords: Public amenities; rent; rental value; residential property; spatial distribution